2020
DOI: 10.1002/leg3.70
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profiles and nutritional quality of four new mungbean lines grown in northern Australia

Abstract: Four new lines of mungbean cultivated under northern Australian cropping conditions (19.8462 S, 147.2448 E) were characterised for yield, seed characteristics, nutritional contents, phytochemical profiles and phenolic acid contents. Their performance was compared to a commercially grown mungbean line (Jade-AU). The seed yield for three of the new lines (AVTMB 1, 3 and 4) was 14% higher compared to Jade-AU. However, the seed size of AVTMB 1 was also significantly smaller compared to the other lines and Jade-AU.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
(52 reference statements)
3
12
1
Order By: Relevance
“…Recent years have seen an expansion of the "functional food" market-where foods are purchased for their health-benefiting effects, rather than as a source of basic nutrition and energy [38][39][40]. For example, the consumption of juice from Queen Garnet plums has been shown to reduce oxidative stress [41] and reduce the risk of blood clot formation in clinical trials [42], while polyphenolics isolated from chickpeas have been found to provide anti-cancer effects, particularly against colorectal cancer [43].…”
Section: Functional Foodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have seen an expansion of the "functional food" market-where foods are purchased for their health-benefiting effects, rather than as a source of basic nutrition and energy [38][39][40]. For example, the consumption of juice from Queen Garnet plums has been shown to reduce oxidative stress [41] and reduce the risk of blood clot formation in clinical trials [42], while polyphenolics isolated from chickpeas have been found to provide anti-cancer effects, particularly against colorectal cancer [43].…”
Section: Functional Foodsmentioning
confidence: 99%
“…There is an ongoing interest in biochemical characterisation and quantification of polyphenols across a wide range of food products, given that compounds from this class have been associated with a wide range of potential health-benefiting effects [151][152][153][154][155], particularly in improving cardiovascular health [156][157][158][159][160]. Consequently, the rapid prediction of total polyphenol content using infrared spectroscopy could have the potential to greatly benefit the effectiveness and robustness of the quality assurance of functional food products [40,96].…”
Section: Polyphenolsmentioning
confidence: 99%
“…Although vitexin is more commonly known to occur in mungbean [ 25 ], it has been previously reported from faba bean using UHPLC-ESI-QTOF-MS-based metabolic profiling [ 26 , 27 ], although it was not quantified. Similarly, although rutin (quercetin-3-rutinoside) does not appear to have been previously reported from faba bean seed, numerous other types of quercetin glycosides have been found in this matrix [ 8 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each methanol extract (20 mL) was concentrated using a rotary evaporator with the water bath temperature limited to 27 °C, before being reconstituted in 1 mL of methanol and syringe filtered (Livingstone 0.45 µm PTFE). The phenolics were separated on an Agilent 1100 HPLC system (Waldbronn, Germany) using previously described methods [ 27 ]. Briefly, a reversed-phase C 18 column (Agilent Eclipse XDB-C18; 150 × 4.6 mm; 5 µm pore size) and guard cartridge (Gemini C 18 4 × 2 mm) were used, with an injection volume of 5 µL and column temperature of 27 ± 0.8 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, separation was achieved on a previously described Agilent 1100 HPLC system (Johnson et al 2020f), with an Agilent Eclipse XDB-C18 column (150 × 4.6 mm; 5 µm pore size), injection volume of 5 µL and detection wavelength of 230 nm. The mobile phase followed a gradient elution at 1 mL/min (A = water, B = methanol), ramping from 30% A to reach 60% at 2 mins, 63% at 10 mins, 65% at 16 mins and 100% A at 28 mins.…”
Section: Hplc Analysis Of Gingerols and Shogaols In Ginger Samplesmentioning
confidence: 99%